PENGARUH PERCEIVED VALUE TERHADAP AFFECTIVE LOYALTY DAN BEHAVIORAL LOYALTY MELALUI CUSTOMER SATISFACTION SEBAGAI VARIABEL PEMEDIASI PADA PENGGUNA CREDIT CARD CO-BRANDING BANK ACEH - Nandiya Deva Puspa Dewi; Sorayanti Utami (Departemen Manajemen, Universitas Syiah Kuala, 2020)
This study aims to analyze the effect of perceived value on affective loyalty and behavioral loyalty through customer satisfaction as a mediating variable for users of the co-branding credit card of Bank Aceh Syariah. The research sample of 159 bank employees was taken by purposive sampling. Data collection uses a questionnaire and then the data is analyzed using statistical path analysis tools. The study found that perceived value has a positive and significant effect on affective loyalty and behavioral loyalty of Bank Aceh co-branding credit card users. Perceived value has a positive and significant effect on customer satisfaction of Bank Aceh's co-branding credit card users. Customer satisfaction has a positive and significant effect on affective loyalty and behavioral loyalty of Bank Aceh co-branding credit card users. The mediating effect of customer satisfaction in mediating the influence of the Perceived Value on Affective Loyalty and Behavioral Loyalty is partial mediation.